Sulfur-Containing Amino Acids as Precursors of Thiols in Anoxic Coastal Sediments - Kiene, Ronald P. (1990)
Sulfur-containing amino acids were examined as precursors for thiols in anoxic coastal sediments. Substrates (10 to 100 μM) were anaerobically incubated with sediment slurries; thiols were assayed as isoindole derivatives by high-performance liquid chromatography; and microbial transformations of thiols, in contrast to their chemical binding by sediment particles, were identified by inhibition with a mixture of chloramphenicol and tetracycline. Methionine and homocysteine were transformed to methanethiol and 3-mercaptopropionate (3-MPA); methionine stimulated mainly methanethiol production, whereas homocysteine generated more 3-MPA than methanethiol. 2-Keto-4-methiolbutyrate yielded results similar to those with methionine, indicating that demethiolation yields methanethiol at the keto-acid level. Glutathione gave rise to cysteine, which was further transformed to 3-mercaptopyruvate and thence to mercaptoacetate and mercaptoethanol. Mercaptoethanol was oxidized to mercaptoacetate, which was biologically consumed. In conclusion, sulfurcontaining amino acids contribute to the range of thiols that occur in anoxic coastal sediments. New metabolic and environmental transformations were identified: the production of 3-MPA as a metabolite of methionine and the transformation of mercaptopyruvate to mercaptoethanol and mercaptoacetate.